Land Redistribution After the Issuance of Presidential Regulation Number 62 of 2023 on Acceleration of Agrarian Reform Implementation - Azam Muhammad Jundi; Fokky Fuad; Sadino; Jamaluddin Mahasari (Journal of Law, Politic and Humanities, 2025)
Agrarian reform is one of the strategic programs of the Indonesian government to create social justice and improve people's welfare, especially in the agricultural sector. The issuance of Presidential Regulation Number 62 of 2023 concerning the Acceleration of the Implementation of Agrarian Reform is an important momentum in this effort. This study aims to analyze the impact of this regulation on the implementation of agrarian reform in Indonesia, as well as to identify the challenges and opportunities that arise after its implementation. The research method used is a qualitative approach with data collection through literature studies, interviews with relevant stakeholders, and analysis of official documents. The data obtained will be analyzed descriptively to provide a comprehensive picture of the implementation of agrarian reform after the issuance of this regulation. This study also involves statistical analysis of the area of land that has been successfully distributed and the number of people who have access to agricultural land. The results of the study show that Presidential Regulation No. 62 of 2023 has provided a significant boost to the acceleration of land distribution, with a 25% increase in the number of beneficiaries compared to the previous year.